2010
DOI: 10.1088/0031-8949/81/02/025301
|View full text |Cite
|
Sign up to set email alerts
|

Scaling laws for large magneto-optical traps

Abstract: Multiple scattering of light has been the main limitation of the maximum atomic density achievable in magneto-optical traps (MOTs). We present a detailed experimental investigation of the size and density scaling laws for large MOTs with up to N = 10 10 atoms, larger than those usually studied in detail. Most of our observations can be explained with previous models and only a few regimes show unexplained deviations. We also propose a new repulsion mechanism, based on the rescattered repumper photons that migh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 23 publications
1
34
0
Order By: Relevance
“…Possible explanations for this behavior included the effect of the magnetic field gradient and high-order multiple scattering of light inside the cloud. A more involved (numerical) model [7] surprisingly led to the same L ∝ N 1/3 scaling, although the calculated density profiles were no longer homogeneous but displayed a truncated Gaussian shape [7]. This model takes into account the nonlinear form of both trapping and shadow forces and the spatial dependence of the interaction force.…”
Section: Vlmot Size Scalingmentioning
confidence: 80%
See 1 more Smart Citation
“…Possible explanations for this behavior included the effect of the magnetic field gradient and high-order multiple scattering of light inside the cloud. A more involved (numerical) model [7] surprisingly led to the same L ∝ N 1/3 scaling, although the calculated density profiles were no longer homogeneous but displayed a truncated Gaussian shape [7]. This model takes into account the nonlinear form of both trapping and shadow forces and the spatial dependence of the interaction force.…”
Section: Vlmot Size Scalingmentioning
confidence: 80%
“…In ref. [7], we have shown that using different techniques to vary the number of atoms (i.e. tuning the intensity or the diameter of a repumping beam) could yield different scaling laws for the MOT size.…”
Section: Vlmot Size Scalingmentioning
confidence: 99%
“…[19]. For typical 85 Rb MOT, δ = −Γ 0 /2 and ∇B = 10 Gcm −1 , we get a density n 0 = 3 × 10 9 cm −3 .…”
mentioning
confidence: 72%
“…The atomic spatial density at the center of the cloud is given by ρ 0 = N/( √ 2πR) 3 . Using the notation r = (x, y, z) = (r ⊥ , z), the optical thickness at the center of the cloud (r ⊥ = 0) is defined as…”
Section: Contributions To the Radiation Pressure Forcementioning
confidence: 99%